(untitled) (European Bison Conservation Newsletter, 2012)
The European bison is the symbol for the whole nature conservation movement focused on threatened and endangered species. Sawed through the captive breeding the European bison is still maintained in captivity but also successfully reintroduced to the wild. This article analyses the reasons for European bison extinction, highlights the restitution phases and the present population. Successful European bison restitution into multiple Protected Areas of Russia is demonstrated; reasons for the decrease of European bison population size throughout Russia in the 1990’s are discussed. Highlighted is an importance of European bison breeding centres – the Prioksko-Terrasnyi biosphere reserve and the Oksky reserve in conservation of its genetic diversity and establishment of new populations. Indicated is the direction to resolve the challenges of European bison restitution in Russia.